1994
DOI: 10.1159/000262018
|View full text |Cite
|
Sign up to set email alerts
|

In situ Remineralization of Root Surface Lesions Using a Fluoride Chewing Gum or Fluoride-Releasing Device

Abstract: The in situ remineralization of early root surface lesions was studied using a fluoride-releasing device (FRD) or a fluoride chewing gum. Root specimens with subsurface lesions were mounted in removable lower appliances in 6 adult subjects. Test groups chewed five sticks/day (0.1 mg F/stick) or one FRD (0.5 mg F/day release rate) was mounted in the midline of the appliance. A fluoride-free dentifrice was used three times/day for each 21-day control and the two test regimens. Separate root lesions were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The fluoride-treated enamel specimens showed a significant-ly better acid resistance, significantly more remineralization, and significantly more F uptake in up to 70 pLm depth (Lamb et al, 1993). Using the same F-containing chewing gum and the same procedure, De Los Santos et al (1994) reported improved remineralization of rootsurface lesions after 21 days with fluoride-containing chewing gum, thus corroborating an earlier study of in vivo remineralization of root-surface caries with fluoridecontaining chewing gum (Lin and Corpron, 1991). Examples of marketed F-containing chewing gums are Fludent®, Fluorette®, Fluogum®, Sensodyne® mit Fluorid, and Lacalut® fluor.…”
Section: Discussionsupporting
confidence: 83%
“…The fluoride-treated enamel specimens showed a significant-ly better acid resistance, significantly more remineralization, and significantly more F uptake in up to 70 pLm depth (Lamb et al, 1993). Using the same F-containing chewing gum and the same procedure, De Los Santos et al (1994) reported improved remineralization of rootsurface lesions after 21 days with fluoride-containing chewing gum, thus corroborating an earlier study of in vivo remineralization of root-surface caries with fluoridecontaining chewing gum (Lin and Corpron, 1991). Examples of marketed F-containing chewing gums are Fludent®, Fluorette®, Fluogum®, Sensodyne® mit Fluorid, and Lacalut® fluor.…”
Section: Discussionsupporting
confidence: 83%
“…Fluoride-containing chewing gum has more than 80 percent oral bioavailability, 3 reduces demineralization and enhances remineralization of enamel. [4][5][6] Fluoridecontaining chewing gum, however, is not available in the United States, although it is elsewhere in the world.…”
Section: Chewing Gum Containing Fluoride Minerals Alkalinizing Agenmentioning
confidence: 99%
“…Previous in situ studies have shown that F chewing gum enhances remineralisation in enamel and dentine [De Los Santos et al, 1994]. F chewing gum has been shown to release F into saliva with a similar pattern as tablets containing the same amount of F [Sjögren et al, 1993;Seppä et al, 1997].…”
mentioning
confidence: 93%